2009
DOI: 10.1161/circulationaha.109.854398
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Intravascular Ultrasound Findings With Histopathological Analysis of Thrombus Aspirates in Patients With Very Late Drug-Eluting Stent Thrombosis

Abstract: Background-Intravascular ultrasound of drug-eluting stent (DES) thrombosis (ST) reveals a high incidence of incomplete stent apposition (ISA) and vessel remodeling. Autopsy specimens of DES ST show delayed healing and hypersensitivity reactions. The present study sought to correlate histopathology of thrombus aspirates with intravascular ultrasound findings in patients with very late DES ST. Methods and Results-The study population consisted of 54 patients (28 patients with very late DES ST and 26 controls).Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
274
0
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 445 publications
(290 citation statements)
references
References 28 publications
10
274
0
6
Order By: Relevance
“…This is thought to be due to a combination of factors including adverse lesion morphology and high thrombus burden, persistent inflammation and increased platelet reactivity, as well as chronic processes associated with delayed healing and vessel remodelling 21 . Additionally, intravascular imaging following DES implantation in STEMI has shown that at follow-up a higher proportion of struts remains uncovered compared to BMS [22][23][24] and that incomplete DES apposition 25,26 is observed more frequently, a finding that appears to indicate adverse vessel remodelling and confer a higher risk of subsequent stent thrombosis. Given this background, BP-DES may represent an attractive solution for patients with STEMI, as complete polymer biodegradation after drug elution is expected to result in a vessel wallstent interaction resembling that seen after bare metal stenting.…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to be due to a combination of factors including adverse lesion morphology and high thrombus burden, persistent inflammation and increased platelet reactivity, as well as chronic processes associated with delayed healing and vessel remodelling 21 . Additionally, intravascular imaging following DES implantation in STEMI has shown that at follow-up a higher proportion of struts remains uncovered compared to BMS [22][23][24] and that incomplete DES apposition 25,26 is observed more frequently, a finding that appears to indicate adverse vessel remodelling and confer a higher risk of subsequent stent thrombosis. Given this background, BP-DES may represent an attractive solution for patients with STEMI, as complete polymer biodegradation after drug elution is expected to result in a vessel wallstent interaction resembling that seen after bare metal stenting.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, under some circumstances or with some DES, DAPT for 3 months could be sufficient but the evidence is not robust [219]. Recent evidence shows that (very) late stent thrombosis results from delayed hypersensitivity to components of the drug polymer device combination that causes necrotizing vasculitis and late malapposition [238]. Diabetics may require a longer duration of DAPT.…”
Section: Drug-eluting Stentsmentioning
confidence: 99%
“…3---8 Delayed neointimal coverage and a hypersensitivity reaction to components of the drug-polymer-stent combination, together with ongoing vessel inflammation, impaired healing and abnormal remodeling leading to late and very late acquired stent malapposition, have been associated with VLST, but the precise mechanism is still unknown. 9---13 Patient-related factors (including compliance with antiplatelet therapy), procedural and post-procedural factors (including type and duration of antiplatelet therapy) probably interact and predispose the patient to ST. 2,3,10 Endothelial dysfunction has also been described as an adverse consequence following coronary DES implantation, although its clinical significance is still unknown. 14 In fact, although DES target vascular smooth muscle cell proliferation and migration (neointimal hyperplasia), the key factors in the development of restenosis, they impair re-endothelialization and promote late in-stent neoatherosclerosis, a new concept whose precise mechanism is also unknown, that acts as another substrate for VLST.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 This also involves both proximal and distal nonstented reference segments and leads to delayed arterial healing, impairment of endothelial nitric oxide synthesis and imbalance between endothelium-derived relaxing and contracting factors, resulting in a thrombogenic environment and paradoxical vasoconstriction of the adjacent segments. 10,16 Moreover, stent-induced mechanical changes in vessel geometry modify its response to endothelial injury and have been linked to the pathobiology of ST. 17 To the best of our knowledge, this is the first report of a VLST, 81 months post-PCI, simultaneously occurring in the three coronary artery territories following discontinuation of antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation